2002
DOI: 10.1124/jpet.300.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Dependence of Salt-Induced Hypertension in Sabra Rats and Role of Renal α2-Adrenoceptor Subtypes

Abstract: This study investigated the importance of the male sex hormone testosterone on salt-induced hypertension, renal ␣ 2 -adrenoceptor subtype distribution, and gene expression in saltsensitive (SBH) male Sabra rats. Comparisons of blood pressure and renal ␣ 2 -adrenoceptor subtype gene expression and receptor densities have been made among sham-operated rats, and gonadectomized rats treated or not with testosterone and submitted to normal or high salt diet for 6 weeks. In intact rats, only ␣ 2B -adrenoceptors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…A similar mechanism has been demonstrated in salt-induced hypertension of Sabra rats, a phenomenon depending on testosterone [21], and also in spontaneously hypertensive rats in which blood pressure decrease after gonadectomy and increases signifi cantly upon dihydrotestosterone replacement [29] . Basal heart rate did not change either after testosterone or nandrolone treatment; this fi nding could be related to baroreceptor adjustment of heart rate according to blood pressure rise in resting conditions.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A similar mechanism has been demonstrated in salt-induced hypertension of Sabra rats, a phenomenon depending on testosterone [21], and also in spontaneously hypertensive rats in which blood pressure decrease after gonadectomy and increases signifi cantly upon dihydrotestosterone replacement [29] . Basal heart rate did not change either after testosterone or nandrolone treatment; this fi nding could be related to baroreceptor adjustment of heart rate according to blood pressure rise in resting conditions.…”
Section: Discussionmentioning
confidence: 80%
“…The infl uence of testosterone on salt-induced hypertension depends on a lower reactivity of ␣ 2 -adrenergic receptors in a rodent model [21] , but central nervous system sodium sensitivity and its effect on the efferent sympathetic system of rats exposed to androgenic steroids has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The greater exacerbation in males might be related to the influence of male hormones because testosterone is required for the full expression of the salt-sensitive hypertension phenotype in some rat models. 38 Afsar 39 recently evaluated hypertensive male patients and reported a negative correlation between testosterone levels and urinary sodium excretion, 39 which could be a mechanism for increased hypertension. Yanes et al 16 reported that castration in male rats reduced intrarenal expression of AGT, mean arterial blood pressure, and proteinuria during salt-sensitive hypertension in the Dahl SS model.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now the mechanisms responsible for mediating sex diff erences in blood pressure depending on the salt content of the diet are still unknown. Possible mechanisms for increasing blood pressure in sodium-loaded animals might be an increased sodium reabsorption [ 16 ] , an increase in gene expression and density of α2-adrenoceptors in the kidney [ 13 ] , and an increased renal cortical angiotensinogen mRNA and protein expression suggesting a locally active intrarenal RAAS (renin-angiotensinaldosterone system). The latter may play a major role in mediating salt-sensitive hypertension [ 19 ] .…”
Section: Blood Pressurementioning
confidence: 99%